PENGEMBANGAN BERTANYA KRITIS BERBASIS INKUIRI (BKBI) UNTUK PEMBELAJARAN KIMIA - Tri Santoso; Leny Yuanita (Pascasarjana Universitas Negeri Malang (UM), 2016)
Abstract: Curriculum 2013 recommended that the learning is done with a scientific approach. The key to the success of this learning approach is the student ability to ask critical questioning. Some studies of chemistry learning show students have difficulty to ask critical questions (Katchevich & Hofstein, 2013; Eshach et al., 2014; Santoso, 2014). These problem can certainly reduce the level of activity of students in constructing their own knowledge based on what is becoming a problem for him. To overcome these problems, it is necessary the development of inquiry learning that involves students asking question during the learning takes place. This article describes the development of learning “critical question - inquiry based for learning Chemistry